An Improved Antenna Group Delay Measurement Method Using a Three-antenna Extrapolation Technique - Lin, Haoyu; Song, Zhenfei; Wang, Xuetian; Gao, Hongmin (Společnost pro radioelektronické inženýrství, 2017)
In order to minimize the error due to multiple reflections between antennas in the conventional group delay (GD) measurement, an improved antenna GD measurement method is proposed. In this method, antenna group delay is measured as a function of distances using a three-antenna extrapolation method. The GD is determined by averaging a set of measured GD values according to a derived multiple-reflection error model. Measurement in frequency band of (1575.42±16) MHz for a circularly polarised helical antenna is presented, which gives the detail measurement procedures and validates the method. The uncertainty evaluation for this measurement was carried out as well, and an expanded uncertainty of 0.20 ns (k = 2) has been achieved. One more measurement example in frequency band of (4000±10) MHz for a standard gain horn antenna with an expanded uncertainty of 0.12 ns (k = 2) is also presented briefly in this paper.
Keywords: Group delay; antenna measurement; three-antenna extrapolation; uncertainty evaluation